Suppression of exercise-induced neutrophilia and lymphopenia in athletes by cystine/theanine intake: a randomized, double-blind, placebo-controlled trial - Murakami, S.; Kurihara, S.; Titchenal, C. A.; Ohtani, M. (Journal of the International Society of Sports Nutrition, 2010)
Intense exercise induces increased blood neutrophil counts and decreased lymphocyte counts, and leads to inflammation and immunosuppression. It was previously reported that cystine and theanine (CT) supplementation by long-distance runners before a training camp suppressed the changes of these blood parameters observed in un-supplemented control subjects after the camp. The purpose of the present study was to determine the effects of CT supplementation on the inflammatory response and immune state before and after intense endurance exercise in long-distance runners at a training camp.